2010
DOI: 10.1074/jbc.m110.125336
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin (mTOR) Activation Increases Axonal Growth Capacity of Injured Peripheral Nerves

Abstract: Unlike neurons in the central nervous system (CNS), injured neurons in the peripheral nervous system (PNS) can regenerate their axons and reinnervate their targets. However, functional recovery in the PNS often remains suboptimal, especially in cases of severe damage. The lack of regenerative ability of CNS neurons has been linked to down-regulation of the mTOR (mammalian target of rapamycin) pathway. We report here that PNS dorsal root ganglial neurons (DRGs) activate mTOR following damage and that this activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
195
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(214 citation statements)
references
References 58 publications
(71 reference statements)
15
195
0
4
Order By: Relevance
“…PI3K/Akt/mTOR signaling has been shown to promote growth and branching in hippocampal neurons [16] . In recent reports, mTOR promoted axonal regeneration in the adult central nervous system and increased the axonal growth of injured peripheral nerves [36,37] . In our experiment, atorvastatin increased the activation of mTOR and p70S6K while rapamycin, an inhibitor of mTOR, decreased the effect of atorvastatin on neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt/mTOR signaling has been shown to promote growth and branching in hippocampal neurons [16] . In recent reports, mTOR promoted axonal regeneration in the adult central nervous system and increased the axonal growth of injured peripheral nerves [36,37] . In our experiment, atorvastatin increased the activation of mTOR and p70S6K while rapamycin, an inhibitor of mTOR, decreased the effect of atorvastatin on neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling molecules have been reported to be both regulated by PP1 and involved in the regulation of neurite growth (Abe et al, 2010;Bito et al, 1996;Gao et al, 2004;Hur et al, 2011;Morfini et al, 2004;Shi et al, 2004;Stegmüller et al, 2008;Thayyullathil et al, 2011;Xiao et al, 2010;Zhou et al, 2004). Dephosphorylation of Akt/glycogen synthase kinase 3 beta (GSK3b), cAMP-response element binding protein (CREB) and TbRI by PP1 regulates the phosphatidylinositol 3-kinase (PI3K), cAMP/PKA and TGF-b/Smad signaling pathways, respectively.…”
Section: Ipp5 Maintains Tgf-b Signalingmentioning
confidence: 99%
“…The level of mTOR activity in CNS neurons declines during development (Park et al, 2008), correlating with the decrease in their regrowth ability. We and others have demonstrated that deletion of phosphatase and tensin homolog (PTEN) or tuberous sclerosis proteins 1/2 in several different types of CNS neurons enhances axonal regeneration, an effect inhibited by mTOR blockade (Park et al, 2008;Abe et al, 2010;Byrne et al, 2014). In contrast, others have reported minimal roles of mTOR in promoting axon regeneration in sensory neurons (Christie et al, 2010), indicating that neurons under different conditions may employ mTOR-dependent or independent mechanisms to trigger axonal regrowth.…”
Section: Introductionmentioning
confidence: 99%